The Influence of Service Quality, Product Price, Corporate Image of Telkomsel Mobile Customer Loyalty Company - Kurniawan, Dede; Ariyanti, Maya; Hidayah, Riski Taufik (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
Purpose – The purpose of this study is to find out how the influence of corporate image, service quality, product price and customer satisfaction on Customer Loyalty.The object used in this study is Telkomsel customers in the work area of the Telkomsel Karawang Branch.Methodology/approach – The method used for sampling is probability sampling. The number of samples was determined using a statistical approach, using the Slovin formula. The collection of sample data will be obtained through the distribution of questionnaires to Telkomsel customers. And the research method used is a quantitative abbreviation with the Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis technique Findings – It was found that from ten hypothesis testing showed that nine hypotheses were accepted in this study and one hypothesis was rejected. . Product prices have a significant effect on customer satisfaction. Prices that are considered commensurate with the benefits increase customer satisfaction but Product price has no significant effect on customer loyalty.